Cortinarius kashmirensis sp. nov. in Cortinarius sect. Disjungendi (Agaricales) from Pakistan - Khurshid, Rubab; Naseer, Arooj; Garrido-Benavent, Isaac; Khalid, Abdul Nasir (Phytotaxa, 2023)
During recent fieldwork at Azad Jammu and Kashmir (Pakistan), many basidiomycetes of the genus Cortinarius were collected from mixed coniferous Himalayan temperate forests. Their morphological characterization and phylogenetic analyses based on ITS and LSU sequence data yielded a well-delimited, new species within C. subgenus Telamonia sect Disjungendi. It is characterized by producing small and dry basidiomata with blackish brown conico-convex pilei when young and uplifted at maturity, dark brown lamellae, a fibrillose stipe and small basidiospores (9.4 × 5.5 µm in average).